Suppression of photocyclization: stabilization of an aggregation-induced tetraaryldistyrylbenzene emitter - Freudenberg, Jan; Rominger, Frank; Bunz, Uwe H. F. (Chemistry - a European journal, 2016)
Abstract The synthesis of 2,3,5,6-tetrakis(2,6-difluorophenyl)di(styryl)benzene by using a conventional synthetic sequence, including Diels?Alder and Horner reactions is reported. The target is an effective aggregation-induced emitter. It is photostable with respect to electrocyclization, due to the presence of the fluorine substituents. This compound undergoes photochemical trans/cis isomerization of its styryl double bonds.